BIOSUPLEMEN SINBIOTIK (PROBIOTIK DAN PREBIOTIK) DALAM SOYGHURT SEBAGAI IMUNOSTIMULAN DAN PENURUN KADAR KOLESTEROL - Rumiyati, Eni; Nurhidayati, Anis (Universitas Sebelas Maret, 2014)
Abstract - The concept of synergistic synbiotics ( prebiotics and probiotics ) recently used for the characterization of foods as biosuplemen health improvement infunctional foodis soyghurt ) One way food fortification fermented yoghurt based on vegetable protein or soy seed with supplementation of probiotics and prebiotics . The purpose of the research was to determine the effect biosuplemen synbiotics( probiotics and prebiotics ) in soyghurt as an immunostimulant and lowering cholesterol levels . The research method consists of three stages: the first stage is the isolation of probiotic from yoghurt fermentation industrial products ; the second stage is biopreparation synbiotics in soyghurt the addition of robiotics : 2 % maltodextrin , FOS 2 % , the mixtures 2 % FOS: Maltodextrin 2 % = 1 : 1 and 2 % Chito - oligosaccharides and probiotics 10 % v / v ( Lactobacillus casei ) ; the third stage is the analysis of fermented product that level of fat, level of protein, levelof microbial contamination and the level of preference ( color , smell , consistency , flavor ) by panelists. The results showed the fortification synbiotics in soyghurt as a functional food can provide immunostimulatory effects of cholesterol - lowering and an effortto reduce the risk of coronary heartdisease . Keywords : biosuplemen , synbiotics , soyghurt , immunostimulant , antihypercholesterolemia